(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The documents are very important sources for researchers and historians to obtain confirmed information about history, and studying the social aspect of any country gives you important information about the political and economic conditions of this country, and most researchers tend to study the political and economic fields and are less in social studies, although the study of Historical events are not accurate without going in to social studies, so I turned in this research to achieve documents from the sharia court in Lattakia to understand the social reality in it in the ottoman era, because this makes the researcher learn about the social situation in all the ottoman states because the Ottoman laws are one and applied in all across the Ottoman Empire.